Sustainable Livelihood Strategies Rural Household in Sanden District Bantul Regency - Pratiwi, Liana Fatma Leslie; Al Rosyid, Ali Hasyim; Kafiya, Maftuh (Proceeding International Conference on Science and Engineering, 2020)
People living in the countryside mostly have a profession as a farmer. Farming is one of the largest sources of income for rural households. In the district of Sanden, rural communities utilize a variety of land agroecosystems for agriculture. Utilization of various types of agricultural land agroecosystem is one of the household livelihood strategies. Livelihood strategies undertaken by rural communities aim to reduce poverty and improve household welfare. This research aims to (1) describe strategy of rural households to support the achievement of sustainable livelihoods (2) Knowing the inequality of farmers ' income distribution based on livelihood strategies used by rural households. The basic method used is a descriptive analytical method. The research site in Sanden district, Bantul regency was then taken by random farmer owners of 30 people as respondents. Rural household strategy to support sustainable livelihood achievement is calculated using descriptive statistics, and the inequality of farmer's income distribution based on livelihood strategies used by rural households is calculated using the Gini index and the Lorentz curve. The results showed that farmers ' household strategy to support the greatest sustainable livelihoods achievement in the form of consolidated strategies, and inequality of revenue distribution based on households livelihood strategies is moderate distribution inequality.